Blockchain technology - current status and future research in healthcare technology - Shmatko, O. V.; Gamayun, I.; Dorohyi, M.; Шматко, О. В. (InterConf, 2024)
Modern society is facing a growing need for safe, efficient, and transparent exchange of patients' personal data in healthcare. Protecting the confidentiality and integrity of medical information is a priority for ensuring high-quality and effective medical care. Blockchain technologies provide a promising tool for solving this problem, allowing you to create a decentralised and secure system for sharing personal patient data. The aim of this work is to ensure a high level of security and confidentiality of medical data, as well as to increase the efficiency of processes in the healthcare sector by developing software components of the patient personal data exchange system based on blockchain technologies. The study's goal is to investigate the system for exchanging patients' personal data in the healthcare sector. The study's subject is software components based on blockchain technologies, designed to ensure the safety, transparency, and efficiency of medical information exchange. Results. This paper proposes an architectural model for a safe and efficient medical data exchange system, suitable for widespread implementation in the healthcare sector. conclusion. The introduction of a secure personal data exchange system based on blockchain technology in healthcare will help improve the quality of medical care and provide medical personnel with faster access to important data. The theoretical significance lies in expanding knowledge about the application of blockchain technologies in healthcare, as well as issues of medical information security and confidentiality. This study can serve as a foundation for further research in this area and contribute to the development of new methods and approaches to medical data exchange.
Keywords: blockchain; personal patient data; IoTM; smart contracts; Ethereum; Medical Data Exchange System Model